2019
DOI: 10.1002/er.4369
|View full text |Cite
|
Sign up to set email alerts
|

Crack propagation of planar and corrugated solid oxide fuel cells during cooling process

Abstract: Summary The corrugated solid oxide fuel cell (SOFC) can effectively improve energy density and transformation efficiency compared with conventional planar SOFC, but its stability and durability have not been systematically analyzed. The residual stress of SOFC may lead to crack initiation and propagation during cooling process, so stress distributions of planar and corrugated SOFCs are simulated to analyze the location of crack initiation. The materials of electrolyte, anode, and cathode in this paper are yttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…Substituting Equations (20) and (21) into Equation (19) gives the displacement equations in terms of Young's modulus as follows, respectively 28 :…”
Section: Navier Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting Equations (20) and (21) into Equation (19) gives the displacement equations in terms of Young's modulus as follows, respectively 28 :…”
Section: Navier Equationmentioning
confidence: 99%
“…The precracks including edge crack and middle crack are introduced into anode-electrolyte interfaces to investigate crack propagation of two types of SOFCs during cooling process. 19 Xie et al determined the material property of the interfacial layer based on the formation mechanism and composition distribution of the interfacial layer, and the analytical solutions of interfacial thermal stresses including both shear stress and peel stress between the electrodes and electrolyte of SOFC are deduced. 20 Wang et al described the temperature profile according to measured temperature points in the stack.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen and air are supplied as fuel and oxygen for the chemical reaction in SOFC, respectively. Generally, nickel (Ni), strontium‐doped lanthanum manganite (LSM), and yttria‐stabilized zirconia (YSZ) are chosen as the materials of the anode, cathode, and electrolyte, respectively 10,11 . The oxygen enters into the cathode and hydrogen enters into the anode during SOFC operation.…”
Section: Oxidation Mechanism Of Oxide Layermentioning
confidence: 99%
“…Results showed that the cermet damaged in an area close to the anode‐electrolyte interface and that a delamination can occur along the interface between the anode functional layer (AFL) and the anode support layer (ASL). Xie et al investigated the crack propagation of planar and corrugated solid oxide fuel cells during cooling process and found that for the corrugated SOFC, the cracks propagate more slowly and the cell is less prone to interfacial delamination compared with planar SOFC.…”
Section: Introductionmentioning
confidence: 99%